Encyclopedia of food sciences and nutrition - Caballero, Benjamin; Trugo, Luiz C.; Finglas, Paul M. (Academic, 2003)
The Encyclopedia of Food Sciences and Nutrition, Second Edition is an extensively revised, expanded and updated version of the successful eight-volume Encyclopedia of Food Science, Food Technology and Nutrition (1993). Comprising ten volumes, this new edition provides a comprehensive coverage of the fields of food science, food technology, and nutrition. Every article is thorough in its coverage, the writing is succinct and straightforward, and the work presents the reader with the best available summary and conclusions on each topic. Easy to use, meticulously organized, and written from a truly international perspective, the Encyclopedia is an invaluable reference tool. An essential item on the bookshelf for every scientist or writer working in the fields of food and nutrition. * Contains over 1,000 articles covering all areas of food science and nutrition * Edited and written by a distinguished international group of editors and contributors * Includes 'Further Reading' lists at the end of each article * A complete subject index contained in one volume * Extensive cross-referencing * Many figures and tables illustrate the text, with a color plate section in each volume.